Deep transcriptome profiling reveals limited conservation of A-to-I RNA editing in Xenopus - Nguyen, Tram Anh (2024)
Background: Xenopus has served as a valuable model system for biomedical research over the past decades. Notably, ADAR was first detected in frog oocytes and embryos as an activity that unwinds RNA duplexes. However, the scope of A-to-I RNA editing by the ADAR enzymes in Xenopus remains underexplored. Results: Here, we identify millions of editing events in Xenopus with high accuracy and systematically map the editome across developmental stages, adult organs, and species. We report diverse spatiotemporal patterns of editing with deamination activity highest in early embryogenesis before zygotic genome activation and in the ovary. Strikingly, editing events are poorly conserved across different Xenopus species. Even sites that are detected in both X. laevis and X. tropicalis show largely divergent editing levels or developmental profiles. In protein-coding regions, only a small subset of sites that are found mostly in the brain are well conserved between frogs and mammals. Conclusions: Collectively, our work provides fresh insights into ADAR activity in vertebrates and suggest that species-specific editing may play a role in each animal’s unique physiology or environmental adaptation.